2009
DOI: 10.3324/haematol.2008.001784
|View full text |Cite
|
Sign up to set email alerts
|

A new mutation in the hepcidin promoter impairs its BMP response and contributes to a severe phenotype in HFE related hemochromatosis

Abstract: BPM-RE. In conclusion, our results suggest that a mutation in the BMP-RE of hepcidin promoter may impact on human iron metabolism.Key words: hepcidin, BMP, hemochromatosis, iron, gene expression. hemochromatosis. Haematologica 2009; 94:720-724. doi: 10.3324/haematol.2008 This is an open-access paper. Citation: Island M-L, Jouanolle A-M, Mosser A, Deugnier Y, David V, Brissot P, and Loréal O. A new mutation in the hepcidin promoter impairs its BMP response and contributes to a severe phenotype in HFE related A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 25 publications
1
43
1
Order By: Relevance
“…It is clinically characterized by hemophagocytic lymphohistiocytosis (HLH), which usually develops in response to an Epstein-Barr virus (EBV) infection, dysgammaglobulinemia and malignant lymphoma. Most cases of XLP are caused by mutation in the SLAM-associated protein (SAP) or SH2D1A [1][2][3] . The X-linked inhibitor of apoptosis (XIAP) is also reported to cause XLP, 4 and at least 9 families with XIAP deficiency have been reported in Europe and the United States.…”
Section: Barton and Colleaguesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is clinically characterized by hemophagocytic lymphohistiocytosis (HLH), which usually develops in response to an Epstein-Barr virus (EBV) infection, dysgammaglobulinemia and malignant lymphoma. Most cases of XLP are caused by mutation in the SLAM-associated protein (SAP) or SH2D1A [1][2][3] . The X-linked inhibitor of apoptosis (XIAP) is also reported to cause XLP, 4 and at least 9 families with XIAP deficiency have been reported in Europe and the United States.…”
Section: Barton and Colleaguesmentioning
confidence: 99%
“…To clarify the differences in the clinical picture of SAP deficiency and XIAP deficiency, a greater number of patients with XLP should be surveyed. Meina Zhao, 1 Hirokazu Kanegane, 1 Kazutaka Ouchi, 2 Toshihiko Imamura, 2 Sylvain Latour, 3 Toshio Miyawaki…”
mentioning
confidence: 99%
“…15 In support of the contribution of regulatory SNPs in hepcidin expression variation and iron metabolism, Island et al found a C>T polymorphism (underlined) in one of two bone morphogenetic protein response elements, BMP-RE, (GGCGCC→GGTGCC) in the promoter that impaired transcription of the gene, its IL-6-responsiveness and binding by Smads. 16 Similarly, Marco et al found association between a -582A>G polymorphism in the hepcidin promoter and iron overload in thalassemia major. 17 Porto et al previously reported a SNP (a G to A substitution) in the 5'UTR of the human hepcidin gene which correlated with severe hemochromatosis.…”
Section: Cis-acting Regulatory Polymorphisms In Hepcidin Expression Lmentioning
confidence: 99%
“…We conclude that routine testing to detect HAMP nc.-153C>T is not indicated in populationbased hemochromatosis and IO screening programs in North America. James C. Barton, 1,2 Catherine Leiendecker-Foster, 3 Honggui Li, 3 Susie DelRio-LaFreniere, 3 Ronald T. Acton, 4 and John H. Eckfeldt, 3 …”
mentioning
confidence: 99%
“…Island and colleagues recently described a 37-year old French man with HFE p.C282Y homozygosity, severe iron overload (IO), and heterozygosity for the novel hepcidin (HAMP) promoter mutation nc.-153C>T. 1 In vitro nc.-153C>T decreased transcriptional activity of the promoter altered its interleukin-6 (IL-6) responsiveness and prevented binding of SMAD1/5/8/4 protein complex to the bone morphogenetic protein-responsive element (BMP-RE) of HAMP. Thus, nc.-153C>T could decrease hepcidin levels and contribute to IO.…”
mentioning
confidence: 99%